Electric field manipulation of particles in leaky dielectric liquids - Rozynek, Z.; Castberg, R.; Kalicka, A.; Jankowski, P.; Garstecki, P. (Archives of Mechanics, 2015)
Patchy colloidal capsules, i.e., hollow structures with permeable heterogeneous surfaces, possess advantageous properties when compared with their homogenous counterparts. For example, owing to specific interactions between patches they can self-assemble into complex structures to form functional materials. Fabrication of patchy colloidal capsules has long been theorized by scientists able to design different models, but the actual production of them remains a challenge. Here, we demonstrate how to manipulate colloidal particles on a surface of a droplet with electric fields. We present three examples of patchy structures formed via electrohydrodynamic microflows and electro-coalescence. In addition, we show electro-orientation of patchy capsules composed of both nonconductive polymeric particles and conductive silver coated particles. Finally, we discuss the importance of an appropriate selection of oils and particles.